2015
DOI: 10.1021/nn504025a
|View full text |Cite
|
Sign up to set email alerts
|

Avasimibe Encapsulated in Human Serum Albumin Blocks Cholesterol Esterification for Selective Cancer Treatment

Abstract: Undesirable side effects remain a significant challenge in cancer chemotherapy. Here we report a strategy for cancer-selective chemotherapy by blocking acyl-CoA cholesterol acyltransferase-1 (ACAT-1)-mediated cholesterol esterification. To efficiently block cholesterol esterification in cancer in vivo, we developed a systemically injectable nanoformulation of avasimibe (a potent ACAT-1 inhibitor), called avasimin. In cell lines of human prostate, pancreatic, lung, and colon cancer, avasimin significantly reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(67 citation statements)
references
References 76 publications
2
64
1
Order By: Relevance
“…Tumor growth was monitored weekly by IVIS imaging by detecting the luminescence signal in vivo . Avasimibe was prepared using a water-soluble formulation by complexing with human serum albumin (32) and intraperitoneally injected at a dose of 15 mg/kg per day. The results showed that avasimibe treatment for 4 weeks remarkably suppressed tumor size, as indicated by luminescence signal intensity (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Tumor growth was monitored weekly by IVIS imaging by detecting the luminescence signal in vivo . Avasimibe was prepared using a water-soluble formulation by complexing with human serum albumin (32) and intraperitoneally injected at a dose of 15 mg/kg per day. The results showed that avasimibe treatment for 4 weeks remarkably suppressed tumor size, as indicated by luminescence signal intensity (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This led to apoptosis and the suppression of proliferation. Systemic treatment of avasimin notably suppressed tumor growth in mice and prolonged survival time 59 . Similarly, SOAT1 inhibition decreased cell proliferation and invasion in two tumor cell lines 60 .…”
Section: Soatmentioning
confidence: 98%
“…In prostate cancer, avasimibe treatment impairs the Wnt-β-catenin pathway and thus suppresses metastasis 111 . Application of avasimin, a nanomedicine version of avasimibe encapsulated with human serum albumin 112 , specifically induces cancer cell apoptosis and is effective in tumour xenograft models.…”
Section: Enhancement Of Cd8 T Cell Function and Inhibition Of The Regmentioning
confidence: 99%